TOOLS OF INTENSIVE ECONOMIC GROWTH ON THE BASIS OF BENCHMARKING: FOREIGN AND RUSSIAN EXPERIENCE - S. V. Ignatyev (Модернизация, инновация, развитие)
Purpose: the main purpose of this article is to explore the possibility of adapting the foreign experience of using benchmarking tools to form promising areas of economic growth, as well as developing a tools for intensive economic growth in Russia and the regions. To achieve this goal, it is necessary to solve the following tasks: to study the basics of intensive economic growth, taking into account the increase in labor productivity and factors of production; to analyze the tools and methods of benchmarking used in foreign practice; to conduct benchmarking of the Russian regions to assess the opportunities for intensive economic growth.Methods: when writing this article, methods of scientific cognition were used, in particular, benchmarking, the method of comparative analysis, the method of system analysis, the graphical method of presenting the results obtained, the method of generalization and systematization of theoretical concepts.Results: in modern conditions, the main source of intensive economic growth is the increase in labor productivity and factors of production. Ensuring the intensity of development at the regional and macroeconomic level can be achieved through the use of benchmarking and analysis of best practices. A comprehensive analysis of the conditions and instruments for intensifying the economy of foreign countries and assessing the applicability / adaptability of world practice for the Russian economy allowed the development of a tools for intensive economic growth in the Russian regions based on the use of tools and principles of benchmarking. Based on the proposed group of indicators for benchmarking to ensure intensive economic growth, the ranking of Russian regions according to the level of socio-economic development was conducted.Conclusions and Relevance: the materials outlined in the article demonstrate the very high efficiency of the use of benchmarking tools to ensure intensive development, which is achieved, first of all, by reducing the differentiation of Russian regions, searching for the most promising and priority innovative directions for further long-term development, allowing to increase the manufacturability of production and labor productivity. The proposed approach to the formation of the tools of intensive economic growth in Russia and regions on the basis of benchmarking is the development of scientific ideas on the improvement of the management of the economy of the regions. The difference between this approach and previously obtained results is that the analysis of the state of the regions is realized taking into account the following elements: conditions / symptoms, premises, tools, results / effects, etc. It is shown that future growth and social welfare of Russia will depend on high-tech industries and services.